STRONTIUM ISOTOPES IN MELT INCLUSIONS FROM SAMOAN BASALTS: IMPLICATIONS FOR HETEROGENEITY IN THE SAMOAN PLUME - Jackson M.G.; Hart S.R. (My University, 2006)
We measured 87Sr/86Sr ratios on 41 olivine-hosted melt inclusions from nine Samoan basalts using laser ablation multi-collector (LA-MC) ICPMS. 87Sr/86Sr ratios are corrected for mass bias after eliminating major isobaric interferences from Rb and Kr. The external precision averages ± 320 ppm (2σ) for the 87Sr/86Sr ratios on natural Samoan basalt glass standards of a similar composition to the melt inclusions. All of the Sr-isotope ratios measured by LA-MC-ICPMS on Samoan melt inclusions fall within the range measured on whole-rocks using conventional methods. However, melt inclusions from two Samoan basalt bulk rock samples are extremely heterogeneous in 87Sr/86Sr (0.70459-0.70926), covering 70% of the variability observed in ocean island basalts worldwide and nearly all of the variability observed in the Samoan island chain (0.7044-0.7089). Seven melt inclusions from a third high 3He/4He Samoan basalt are isotopically homogeneous and exhibit 87Sr/86Sr values from 0.70434 to 0.70469. Several melt inclusions yield 87Sr/86Sr ratios higher than their host rock, indicating that assimilation of oceanic crust and lithosphere is not the likely mechanism contributing to the isotopic variability in these melt inclusions. Additionally, none of the 41 melt inclusions analyzed exhibit 87Sr/86Sr ratios lower than the least radiogenic basalts in Samoa (87Sr/86Sr = 0.7044), within the quoted external precision. This provides an additional argument against assimilation of oceanic crust and lithosphere as the source of the isotopic diversity in the melt inclusions. The trace element and isotopic diversity in Samoan melt inclusions can be modeled by aggregated fractional melting of two sources: A high 3He/4He source and an EM2 (enriched mantle 2) source. Melts of these two sources mix to generate the isotopic diversity in the Samoan melt inclusions. However, the melt inclusions from a basalt with the highest 3He/4He ratios in Samoa exhibit no evidence of an enriched component, but can be modeled as melts of a pure high 3He/4He mantle source. © 2006 Elsevier B.V. All rights reserved.
Keywords: 87SR/86SR; EM2; FOZO; LASER ABLATION; MC-ICP-MS; MELT INCLUSION; PHEM; SAMOA